1999
DOI: 10.1084/jem.189.9.1437
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Nature of Specific Immunological Activity of Tumor-derived gp96 Preparations

Abstract: Mice immunized with optimal doses of autologous tumor–derived gp96 resist a challenge with the tumor that was the source of gp96. Immunization with quantities of gp96 5–10 times larger than the optimal dose does not elicit tumor immunity. This lack of effect is shown to be an active, antigen-specific effect, in that immunization with high doses of tumor-derived gp96, but not normal tissue–derived gp96, downregulates the antitumor immune response. Furthermore, immunization with fractionated doses of gp96 elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 21 publications
3
90
0
Order By: Relevance
“…4A, a dose-dependent adjuvant effect was observed for gp96 in the ELISPOT assay, with the peak activity at 10 g, but gp96 alone had no CTL response. Higher amounts (50 g) of gp96 were detrimental to the adjuvant effect, presumably due to the fact that excess gp96 might be immunosuppressive and decreased the capability of mice to generate an immune T cell response, which was also consistent with a previous report (31). BSA, as a negative control, was unable to provide any adjuvant effect.…”
Section: Adjuvant Effects Of Gp96 and Its Terminal Fragmentssupporting
confidence: 79%
“…4A, a dose-dependent adjuvant effect was observed for gp96 in the ELISPOT assay, with the peak activity at 10 g, but gp96 alone had no CTL response. Higher amounts (50 g) of gp96 were detrimental to the adjuvant effect, presumably due to the fact that excess gp96 might be immunosuppressive and decreased the capability of mice to generate an immune T cell response, which was also consistent with a previous report (31). BSA, as a negative control, was unable to provide any adjuvant effect.…”
Section: Adjuvant Effects Of Gp96 and Its Terminal Fragmentssupporting
confidence: 79%
“…The extent of elevated gp96 expression in liver tissues was significantly correlated with the disease progression of HBV infection, but high level expression of gp96 did not induce an immunoresponse against HBV infection as expected [13]. Other studies involving gp96 as adjuvant have also indicated that highdose gp96 administration can down-regulate inflammatory events and anti-tumor effect [14,15]. This result has been attributed to the activation of Treg or myeloid suppressor cells.…”
mentioning
confidence: 69%
“…[22][23][24][25] When administered exogenously to APCs, the peptides transported by HSPs are very efficiently presented by MHC class I molecules. Peptides complexed to HSPs in vitro, [26][27][28] as well as HSP-peptide complexes purified from cells expressing viral proteins 29,30 or tumor cells, [31][32][33][34][35] induce specific CTL responses. Finally, recombinant HSP-antigen fusion proteins 36,37 were able to elicit CD4 þ -independent CD8 þ cytotoxic T-lymphocyte (CTL) responses.…”
Section: Introductionmentioning
confidence: 99%